Physical Damages Warranting Compensation According To The Civil Liability System In The Nuclear Field (International Journal of Environmental Sciences, 2025)
Using an analytical methodology, the study examined the scope of bodily injuries eligible for compensation under the civil liability regime in the nuclear field. The findings revealed that the scope of compensable bodily harm resulting from nuclear damage includes, primarily, death, as well as non-fatal personal or bodily injuries, whether such injuries are direct or indirect, along with the subsequent damages arising therefrom. Compensation for bodily harm, regardless of its type, generally does not present legal challenges when the damage is immediate. However, in cases of delayed harm, it becomes necessary for the competent court and the trial judge to rely on medical evidence to establish the causal link between the injury and the harmful act.The study recommended the establishment of clear and specific criteria for determining bodily injuries eligible for compensation under civil liability for nuclear damage, given the special nature of such liability. It also emphasized the importance of adopting all safety, security, and protection measures to safeguard workers in the nuclear field in particular, and the public in general.